(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides detailed information on the advantages of multimodal teaching in English language classes. It analyzes the unique aspects of teaching through a multimodal approach that encompasses various learning styles of students, including its effectiveness in developing listening, speaking, reading, and writing skills. The article also explores the additional value brought to the language learning process by using modern technologies, such as mobile apps, online courses, virtual reality, and augmented reality applications. Practical advice is also offered to teachers on how to effectively apply multimodal teaching methods. Highlighting the advantages and future opportunities of this approach in English language classes, the article emphasizes the role of multimodal teaching in enhancing the quality of education.